Evolution of gut microbial community through reproductive life in female rabbits and investigation of the link with offspring survival. (18th November 2020) - Savietto, D.; Paës, C.; Cauquil, L.; Fortun-Lamothe, L.; Combes, S.
Abstract : The digestive microbiota plays a decisive role in shaping and preserving health throughout life. Rabbit younglings are born with a sterile digestive tract but then it gets progressively colonised by the microbiota of the nursing mother, by entering in contact with or ingesting the maternal droppings present in the nest. Here we posit that (i) offspring survival and (ii) lifespan of female rabbits are linked to how diverse their microbiota are. To test the hypothesis that maternal microbiota evolves in females having had different levels of offspring survival in their lifetime, we obtained 216 hard faecal samples from 75 female rabbits at ages 19.6, 31.6, 62.6 and 77.6 weeks. The annual mean offspring survival (MOS ) at 64 days was calculated for each female then crossed against three alpha-diversity indexes (operational taxonomic units (OTU s), inverse Simpson index and Shannon index). Age was also analysed against these three parameters. The alpha-diversity indexes of the female faecal microbiota did not correlate with MOS, but they did decrease with age (e.g. from 712 OTUs at age 19.6 weeks to 444 OTUs at 77.6 weeks; P < 0.05). The age effect was also found in beta-diversity non-metric multidimensional scaling plots using the Bray–Curtis dissimilarity index and the unweighted UniFrac index but not for MOS. The ability of the microbiota composition from the faecal samples of young females (19.6 weeks old) to predict their lifespan was also evaluated. After subdividing the initial population into two classes (females that weaned a maximum of three litters and females living longer), we found no clear distinction between these two classes. To our knowledge, this is the first long-term study to characterise the gut microbiota of adult female rabbits through their reproductive life, thus laying foundations for using the gut microbiota data and its influence in studies on adult rabbits.